2012
DOI: 10.1371/journal.pone.0053422
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Natural Variation in Bermudagrass (Cynodon dactylon) Reveals Physiological Responses Underlying Drought Tolerance

Abstract: Bermudagrass (Cynodon dactylon) is a widely used warm-season turfgrass and one of the most drought tolerant species. Dissecting the natural variation in drought tolerance and physiological responses will bring us powerful basis and novel insight for plant breeding. In the present study, we evaluated the natural variation of drought tolerance among nine bermudagrass varieties by measuring physiological responses after drought stress treatment through withholding water. Three groups differing in drought toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
135
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(138 citation statements)
references
References 38 publications
3
135
0
Order By: Relevance
“…Analysis of natural variations of drought stress tolerance revealed that different bermudagrass cultivars exhibited varied tolerance to drought stress. [1][2][3] Exogenous application of small molecules could effectively alleviate damages caused by multiple abiotic stresses, including drought, salt and cold. [4][5][6][7][8] Exogenous ABA treatment improved drought stress tolerance in 'TifEagle' cultivar through induction of H 2 O 2 and NO, which, in turn, enhanced antioxidant enzyme activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of natural variations of drought stress tolerance revealed that different bermudagrass cultivars exhibited varied tolerance to drought stress. [1][2][3] Exogenous application of small molecules could effectively alleviate damages caused by multiple abiotic stresses, including drought, salt and cold. [4][5][6][7][8] Exogenous ABA treatment improved drought stress tolerance in 'TifEagle' cultivar through induction of H 2 O 2 and NO, which, in turn, enhanced antioxidant enzyme activities.…”
mentioning
confidence: 99%
“…9 Further studies showed that abiotic stress treatments changed antioxidant enzyme activities, ROS contents, osmoprotectant contents (sugar, sucrose, dehydrin, proline), and photosynthesis. [1][2][5][6][10][11][12][13][14] Recently, proteomics and metabolomics approaches have been successfully used to detect omic level changes during bermudagrass stress responses. Under water-deficit condition, 32 proteins had increases in the abundance and 22 proteins exhibited decreases in the abundance, which were mainly involved in metabolism, energy, cell growth/division, protein synthesis and stress defense.…”
mentioning
confidence: 99%
“…Hierarchical cluster analysis was performed using the CLUSTER 3.0 program by the uncentered matrix and complete linkage method following the protocol of de Hoon et al (2004). The resulting tree figure was displayed using the software package, Java Treeview, as described by Chan et al (2012).…”
Section: Hierarchical Cluster Analysismentioning
confidence: 99%
“…In addition, the electrical conductivity of Milli-Q water (E3) was also measured. The REL was calculated using the equation: REL (%) (E1 -E3)/ (E2 -E3) × 100% [26].…”
Section: Measurement Of Membrane Permeabilitymentioning
confidence: 99%